Letter to Alexander Wheelock Thayer regarding rent payments (3 June 1856) (2023)
Autograph letter in English dated June 1862, sent from Marienvilla, Bad tVöslau, to Alexander Wheelock Thayer regarding rent payments to Count Mottett, signed "J. M." (?)